The Migration Diary of a Knickpoint in a Channelized Stream With a Cohesive Bed. Issue 4 (29th April 2019) - Papanicolaou, A. N. (Thanos); Thomas, John T.; Wilson, Christopher G.; Abban, Benjamin K. B.; Bettis, E. Arthur; Elhakeem, Mohamed
Abstract: This paper examines the coevolutionary roles of variable flow features and heterogeneous substrates on knickpoint migration. A conceptual model is used to depict distinct migration mechanisms in a channelized headwater system of a representative intensively managed watershed in the Deep Loess Region of the U.S. Midwest. Throughout this region, entrenched streams have eroded into alluvial‐based strata that are horizontally consistent but vertically heterogeneous. Variable flow in these streams switches between vented conditions, where water shoots from the knickpoint face as an aerated plunging jet, and unvented conditions, where water clings close to its face through suction. These switches affect hydrodynamic mechanisms controlling migration but cannot explain fully observed alternating slow‐fast migration rates. It is hypothesized that vertically heterogeneous strata in entrenched streams, specifically strong‐over‐weak layers, facilitate observed changes in knickpoint migration rates. Preferential erosion of weaker sublayers is thought to trigger other erosional mechanisms to accelerate migration even at low flows. Herein, a migration "diary" documents a representative knickpoint's displacement over time with flow measurements and site stratigraphy. Slower migration occurred from 2006 to 2009 through fluvial erosion of a resistant silt loam cap. From 2009 to 2012, migration accelerated as the knickpoint face reached a critical height through scour. A flow back roller formed, which preferentially eroded a weaker sand sublayer. Undercutting/cantilever failure cycles persisted, causing 30 m of retreat within 2 months (i.e., 62.5% of the total migration over 78 months). Comparisons with established fluvial hydraulics‐based and undercutting/cantilever‐based migration models confirm the hypothesis and importance of both stratified substrates and hydrodynamic controls on knickpoint migration. Key Points: A conceptual sketch is used to depict distinct knickpoint migration mechanisms in a channelized semicohesive stream Knickpoint migration in semicohesive streams is governed by coplay of flow and stratigraphic controls that can change in space and time Heterogeneity in substrate properties can lead to preferential erosion of material, controlling the mechanisms that drive the migration